DESIGN AND DEVELOPMENT OF THE EKSPERTO APP: AN ON-DEMAND SERVICE PROVIDING APPLICATION - Billy S. Javier; Julieta B. Babas; Leo P. Paliunan; James Karl A. Agpalza (Proceedings on Engineering Sciences)
Responding to the need for a unified platform, this project generally aims to analyze, design, development, pilot test, asses and implement a mobile and web application geared at empowering knowledgeable and skilled professionals through employment and reinforced training opportunities. This on-demand integrated service-providing web application responsive to mobile phones was developed through secure web technologies maximizing data mining techniques and recommender module guided by an agile development model. As a service-oriented platform for displaced workers or industry professionals in the locality and service requesting parties, individuals, as well as private or government organizations, this crowdsourcing app for requested services by the community and as an outsource app for skilled and professional workers to market their portfolio or competencies and expertise, utilized a recommender module, providing commonly requested services as well as readily available service provider. The descriptive-development maximizing science research design reinforced by the software development tools were maximized in this study. The EKSPERTO App features a functional dashboard for service-requesting parties, hiring employers, service providers, and government’s arm for job facilitation. The application conformed with indicators of the ISO 25010:2011 and the indicators of the Unified Theory of Technology Acceptance Model critical at understanding, designing, and developing the EKSPERTO App. The project generally benefits the displaced workers and skilled professionals as well as requesting parties or individuals needing on- demand services. Collaborating agencies DOLE and Local Government Units and other work-related agencies will also benefit from the project towards program and policy development for displaced workers and related concern.